Teaching strategies for rehabilitation curriculum: coping with the Covid-19 situation - Afzal, Binash; Mumtaz, Nazia; Rehman, Syed Shakil Ur; Saqulain, Ghulam (Journal of the Pakistan Medical Association, 2022)
The novel corona virus pandemic culminated in a global emergency shutting down educational institutions with recommendations of distant learning. Developing countries like Pakistan faced challenges in terms of keeping the education stream running. The current narrative review was planned to discuss the teaching strategies adopted by various institutes for coping with the situation created by the coronavirus disease-2019. Literature search was done using search engines and databases with key words ‘Academics’, ‘Coping strategies’, ‘Covid-19’, ‘Online learning’, ‘Rehabilitation curriculum’ and their combinations. As a result, 37 articles were analysed for education involving conformation of curricula to social distancing protocol, and use of video-conferencing software, practical rehabilitation curriculum delivery, and evaluation methods. Developing countries, like Pakistan, should upgrade and revise their rehabilitation curriculum at theoretical and practical levels and try to convert the adversity of the pandemic into an opportunity to develop standardised e-learning programmes and software compatible.